Increased Expression of Inducible Cyclooxygenase-2 in Human Endothelial Cells by Antiphospholipid Antibodies - Habib, Aïda; Martinuzzo, Marta E; Carreras, Luis O; Lévy-Toledano, Sylviane; Maclouf, Jacques (Thrombosis and Haemostasis, 1995)
The effect of IgGs from 4 patients with antiphospholipid antibodies and elevated excretion of urinary 11-dehydro-thromboxane B2 was evaluated on the production of prostacyclin by human endothelial cells in culture. After 6 h incubation, there was no change in 6-keto-prosta-glandin F1α in the supernatant. However patients’ IgGs induced a marked increase in cyclooxygenase (Cox) activity compared to IgGs from 2 normal individuals or a commercial pool of IgGs from normal donors, tested by adding exogenous arachidonic acid. Western blot analysis of the cellular Cox content using antibodies specific for the different forms of the enzymes revealed that patients’ IgGs stimulated the synthesis of the newly described inducible Cox-2 without affecting the constitutive Cox-1. This effect was partially neutralized by preincubating the IgGs with phospholipids. The induction was dependent on the amount of IgGs; it was visible at 2 h and persisted up to 24 h. Analysis of mRNA levels showed a pattern of variation in good agreement with the results obtained for protein. The protein kinase inhibitor H-7 or long-term incubation of cells with PMA strongly reduced the induction. These results suggest that antiphospholipid antibodies may not prevent the potential of the vascular cells from generating higher amounts of prostacyclin in response to acute episodes of thrombosis.